Information management sources and other studies: essays in honour of professor K Navlani - Navlani, K; Malhan, I V (Ed.); Shokeen, Ashu (Ed.) (New Delhi Ess Ess, 2001)
This collection of essays is a collaborative ordering to honour Professor Krishna Navlani on her 65th birthday.
Keywords: Information resources; Management; Management information systems; Library administration